Thermodynamic analysis of CO2 blends for vehicle heat pump at cold ambient temperature - Li, Chengyu; Liu, Zhaoqiang; Sun, Binbin; Wang, Youtang; Gao, Song; Zhang, Tiantian; Wang, Baolong (Frontiers in Energy Research, 2022)
The use of heat pump is a promising way of energy conservation to improve the driving range of electric vehicles. In this study, the thermodynamic characteristics of CO2–based blends in the operation of a subcritical heat pump cycle are evaluated at different ambient temperatures considering two operation modes. Coefficient of performance (COP) and volumetric heating capacity (VHC) are used to evaluate heat pump performance. Optimization and comparison of both transcritical and subcritical cycles are conducted using various refrigerants. The results indicated that CO2/R32 (50/50) always outputs higher COP than CO2 or other mixtures. The COP of CO2/R41 (90/10) is inferior to that of CO2 in a transcritical cycle due to the more power consumption of compressor. The blends of R1234yf and R152a with low GWP have lower COP, but a much lower operation pressure is also achieved. CO2 blends have larger VHC, which facilitates simple cycle configuration and compact compression.